Keaslian Budaya Nagari Pariangan Sebagai Daya Tarik Wisata - Novita, Yulia; F, Fatmawati; Eriza, Echa; Arijati, Disty Gusvalinda (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Nagari Pariangan, located in Tanah Datar Regency, is widely recognized as one of the most beautiful villages in the world according to Budget Travel (2012). This recognition is driven not only by its natural landscape but also by the preserved authenticity of Minangkabau culture, which serves as a vital asset for tourism development. This study aims to examine the forms of cultural authenticity maintained by the local community and their contribution to tourism attractiveness. A qualitative descriptive method was employed through field observation, interviews, and documentation. The results of the research show that traditional customs, rumah gadang architecture, the nagari social system, and religious cultural rituals significantly reinforce the image of Pariangan as a cultural tourism destination. These cultural assets provide a strong local identity while supporting sustainable tourism development. Therefore, preserving local cultural authenticity is essential to maintain Nagari Pariangan’s reputation as the most beautiful village in the world and to enhance the well-being of the local community.